Immunocytochemical Profiling of CD4+, CD8+, and CD3+ T Cell Subsets: Clinical Implications in Rheumatic Diseases, Respiratory Disorders, and Oncology - Chen, Junlin; Gong, Liangju; Jiang, Can; Xie, Yuxuan; Wang, Ying; Lu, Lu; Liu, Qing (Trends in Immunotherapy, 2025)
Immunocytochemical staining has emerged as a cost-effective and minimally invasive method for profiling T cell subsets (CD4+, CD8+, and CD3+) in the clinical setting. The quantification of T lymphocyte subsets has become a critical tool for assessing immune dysregulation in chronic inflammatory and autoimmune diseases. This study evaluates the utility of this method in monitoring immune dysregulation across rheumatic diseases (systemic lupus erythematosus—SLE, rheumatoid arthritis—RA, Sjögren’s syndrome—SS), respiratory disorders, and malignancies. Peripheral blood samples from 12 patients (10 of whom had rheumatic diseases, one with lung cancer tested seven times and one with liver cancer tested five times) were collected in EDTA-K2 tubes and analyzed using standardized immunocytochemical protocols. Key findings include: (1) CD4+/CD8+ ratio inversion (<1.0) correlates with disease activity in SLE (OR = 3.2 for lupus nephritis) and predicts lymphoma risk in SS (HR = 2.8). (2) In RA, reduced Th17 proportions post-methotrexate therapy (12.3%→6.8%, p < 0.01) reflect inflammation suppression, while TNF-α inhibitors improve CD4+/CD8+ ratios alongside DAS28 scores (p = 0.003). (3) In oncology, longitudinal CD3+ T cell counts (136–504 cells/μL) and CD8+ dynamics mirror tumor burden and immunotherapy efficacy. Compared to flow cytometry, immunocytochemical staining offers practical advantages for routine clinical use, though limitations in functional subpopulation resolution persist. Integrating these assays with multi-omics approaches may refine personalized treatment strategies. This study underscores the pivotal role of T cell subset analysis in bridging mechanistic immunology with precision medicine.